Legal Reform for Passive Euthanasia in Indonesia: A Comparative Analysis of Policy and Ethics - Ezenduka, Uzodinma Yurriens; Halder, Debarati (Journal of Law and Legal Reform, 2025)
This study aims to elaborate on the ethical and legal problems concerning passive euthanasia and Advance Directives (ADs) in Indonesia, focusing on the legal obscurity in current legislation, which causes uncertainties among families and medical practitioners. Although Indonesia’s Penal Code criminalizes active euthanasia, it remains silent on passive euthanasia, making healthcare providers vulnerable to the risk of prosecution when withholding or withdrawing futile treatments. Using a normative juridical approach, this research primarily analyzes Indonesian statutes and compares them with those of India, Saudi Arabia, and Iran. Despite provisions in health laws for patients to refuse treatment, the absence of explicit guidelines forces healthcare providers to operate with legal uncertainty. A comparative analysis of India’s legalization of passive euthanasia showcases how legislative clarity can align with ethical, medical, and societal needs. Insights from Islamic-majority countries like Saudi Arabia and Iran also reveal that Islamic jurisprudence, through the harm reduction principle, can be aligned with passive euthanasia within an ethical framework. Several particular reform recommendations are provided in this regard in the study, comprising amending the Penal Code to differentiate passive euthanasia and murder, establishing formal AD procedures, and introducing ethics committees and dual-approval oversight to maintain the ethical purity of the process. These reforms and public awareness initiatives would enhance the principle of patient autonomy and clarify misconceptions and legal responsibilities, providing overall improvement in an unattended aspect of medical care.